2006
DOI: 10.1111/j.1742-7843.2006.pto_531.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Channels‐Mediated Vasorelaxation of Rat Aorta Induced by Resveratrol

Abstract: Resveratrol, a phenolic substance present in grapes and a variety of medical plants, has been reported to induce vasorelaxation, however the mechanisms are uncertain. In this paper we investigate the possible participation of K π channels in the endothelium-independent vasodilatation of rat aorta induced by resveratrol. Resveratrol induced concentration-dependent relaxation of rings with endothelium and without endothelium. We used different potassium channel inhibitors to determine whether the K π channels me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 31 publications
4
62
1
Order By: Relevance
“…115 Resveratrol induced concentration-dependent relaxation of rat aortic rings with and without endothelium and margatoxin-sensitive K(+) channels located in the smooth muscle of rat aorta mediated this relaxation effect. 116 The same group repeated the study using endothelium-independent human internal mammary artery (HIMA) obtained from male patients undergoing coronary artery bypass surgery, and a similar conclusion was reached. 117 Resveratrol also inhibits the production of endogenous vasoconstrictors.…”
Section: Effect On Vasorelaxationmentioning
confidence: 71%
“…115 Resveratrol induced concentration-dependent relaxation of rat aortic rings with and without endothelium and margatoxin-sensitive K(+) channels located in the smooth muscle of rat aorta mediated this relaxation effect. 116 The same group repeated the study using endothelium-independent human internal mammary artery (HIMA) obtained from male patients undergoing coronary artery bypass surgery, and a similar conclusion was reached. 117 Resveratrol also inhibits the production of endogenous vasoconstrictors.…”
Section: Effect On Vasorelaxationmentioning
confidence: 71%
“…K V 1.1 and K V 1.6 channels were detected in smooth muscle cell of rat aorta and rat pulmonary artery, but not in smooth muscle cells of mesenteric artery (36,40). In prior experiments, we found that margatoxin abolished resveratrol-induced relaxation of human internal mammary artery and rat aorta (7,16). However, in the present study, margatoxin used in a concentration (10 nM) sufficient to block K V 1 channels did not change the resveratrol-induced relaxation, suggesting that K V 1 channels are not involved in the mechanism of resveratrol-induced endothelium-independent vasodilatation of rat mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in different experimental models, resveratrol can activate adenylate cyclase and membrane-bound guanylyl cyclase and inhibit cGMP-specific phosphodiesterse-5 (13 -15). Previously, we have shown that resveratrol produces relaxation of the isolated human internal mammary artery and rat aorta by activation of margatoxin-sensitive voltage-dependent K + (K V ) channels located in the smooth muscle (7,16). In contrast, Orsini et al (17) suggested that resveratrol derivates inhibited K V channels in the F-11 neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that Res relaxes many types of vascular beds without endothelium through the activation of different types of K + channels. The voltage-dependent K + channel plays an important role in the vasodilatation induced by Res in the aorta (6) and internal mammary artery (9), whereas, the voltage-dependent K + channel is involved in the vasodilatation induced by Res in the thoracic aorta (6). In addition, Res has been shown to induce relaxation of the abdominal aorta through activation of ATP-sensitive K + channels and Ca 2+ -activated K + channels (7).…”
Section: Discussionmentioning
confidence: 99%